Study on the inclusion of two microstrip square open loop resonator to produce a diplexer / Nor Azzahra Ibrahim - Ibrahim, Nor Azzahra (2015)
In this paper, a microstrip square open loop resonator as one of the design for band pass filter is proposed to develop the diplexer. A combination of two microstrip open loop resonator connected to T-junction will produce a diplexer. The microstrip square open loop resonator is operating at two frequencies, 1800 MHz and 2150 MHz. Comparisons between simulated and measured result shows a shifting in return loss, Sn and insertion loss, S2i. From the results, simulated result shows a better return loss and insertion loss.